The "Anglo-Saxon Style" of Journalism - Kennedy, George (2022)
Discusses the introduction of the Anglo-Saxon style of journalism in Spain during the late 1970s. Key components of the Anglo-Saxon style of journalism; Comparison with the traditional journalism of Spain; Implications on communication.